Health Cadres Commitmentin Child Health Care in Moslem Society of Banyumas District - Solikhah, Umi; Kusnanto, Hari; Haryanti, Fitri (International Conference of Moslem Society, 2016)
Community empowerment with regard to maternal and child health services at the community level carried out by cadre.Cadre is health volunteers, selected by the community.404 number of active cadres in primary health care of South Purwokerto entirely female, although it may be a cadre of men. Active cadre toddler actively providing services every month for child before 5 years age. Interest to know the various reasons committed cadres in performing their duties. The method used is qualitative study,to describe a variety of reasons commitment to perform cadre duties in child health care. Retrieving data using interview techniques through the focus group discussion. Data from 30 cadres.Results of interviews taken until the data saturation, as a reason believed by cadres in the commitment to carry out tasks of serving the Muslim community. Characteristic respondent are mean of age 38 years (the youngest age of 25 years and the oldest 55 years old), a 100% Islamic religion, level of education majority of senior high school(at least primary school). Educational level health cadres in Banyumas has met the minimum requirements by the WHO.Results of the analysis showed thatcommitment includes a cadre of dedicated, caring community, a desire to learn, social esteem, individual satisfaction, togetherness, organization, and spirituality. The spirit of cadre to the community need the attention of the government for development and prosperity in accordance with their duties.Spiritual reasons become one of the motivations in providing health services to the community, albeit to a spirit of dedication and a great desire to learn. Cadres continue to provide services, even to families with different spiritual.